Case Report of an 18 Year Old Girl with Solid Pseudo-papillary Tumor of Pancreas - Sigdel, S.; Niroula, S.; Sapkota, G.; Chang, L. H.; Mishra, R. (Kathmandu University Medical Journal, 2020)
Solid Pseudo-papillary Tumor (SPT) of the pancreas is a rare tumor which typically affects young women without any significant clinical symptoms. Solid Pseudo-papillary Tumor usually shows an indolent behavior and only rare cases recur and/or metastasize after complete resection. Here is a case report of 18 years old girl who presented to our centre with complaints of severe epigastric pain and underwent pancreatic parenchyma saving surgery for a large pancreatic head mass. In conclusion, Solid Pseudo-papillary Tumor being a large tumor possess a low malignant potential in which R0 resection has excellent prognosis.